Effects of interruptions for public holidays in Spain on radiotherapy treatments. (September 2016) - de la Vega, J.M.; Ríos, B.; del Río, J. Torres; Guerrero, R.; Castillo, I.; Guirado, D.
Abstract : Introduction: In Spain there are 14 public holidays (PH) per year in which radiotherapy treatments are not administered. This reason causes 45% of the unscheduled stops registered in our department and a loss in local control probability (LCP) of the disease, or the increase of likelihood of biochemical failure (BF) in cases of prostate tumors. Purpose: Our department has an interruptions management program since 2011. This work shows the benefit that it would have been obtained on 2292 radiotherapy treatments (1 March 2011 to 15 August 2015) if treatments had not stopped on PH. Materials and methods: To study the impact of PH working, the disappearance of these interruptions in each patient will be simulated. This will cause overall treatment time (OTT) to decrease. This decrease in OTT will result in an improvement of the LCP, or a decrease in BF. This absolute improvement, named B treat, is calculated from the published data of the influence of OTT in final outcomes of radiotherapy combined with the OTT data obtained in our patient sample. Results: The mean value of B treat are: 1.7%, 1.5%, 0.5%, 0.7% and 1.1% for head and neck, lung, cervix, breast and prostate cancer respectively. In addition 13.3%, 11.1%, 0.0%, 7.9% and 9.4% of these treatments had a B treat  > 4% due to PH working. Conclusion: The effects of PH working improve the outcome of fractionated radiotherapy in certain pathologies, specially HN, lung and prostate cancer, with a relatively low cost and could be implemented in any radiotherapy service.